Prospective case-controlled sound localisation study after cochlear implantation in adults with single-sided deafness and ipsilateral tinnitus - Mertens, G.; Desmet, J.; De Bodt, M.; Van de Heyning, P. (Clinical otolaryngology, 2016)
Objectives To analyse the sound localisation skills of subjects with profound single‐sided deafness (SSD) and accompanied ipsilateral tinnitus who are using a cochlear implant (CI) for between 4 and 11 years. Design Sound localisation skills were tested using nine loudspeakers in a frontal semicircle ranging from −90° to +90°. Subjects were tested in the CION and the CIOFF conditions via 3 localisation stimuli: broadband noise (BB), low‐pass noise (LP) and high‐pass noise (HP). Participants The test group consisted of 10 adult subjects with profound sensorineural SSD, ipsilateral tinnitus and a CI. Normative data of a control group of 30 normal hearing subjects were used for comparison. Main outcome measures Sound location accuracy was analysed via the root‐mean‐square error (RMSE), the mean absolute error (MAE), the localisation bias (‘b’) and the bias‐adjusted deviation (‘db’). Subjective dynamic aspects of hearing were assessed via a reduced version of the Speech, Spatial and Qualities of Hearing Scale (SSQ5). Results For all 3 stimuli, the RMSE improved significantly in SSD subjects in the CION condition compared to the CIOFF condition. The localisation accuracy of subjects with SSD improved significantly for BB and HP stimuli. A significant bias‐adjusted deviation ‘db’ was found for the BB and HP stimuli. Subjects’ mean SSQ5 scores were significantly higher in the CION condition at test date than in the CIOFF condition preoperatively. Conclusions Subjects can better locate sound in the CION condition than in the CIOFF condition.